Edukasi Keamanan Informasi untuk Mendukung Penguatan Literasi Digital Siswa SMA Negeri 8 Tangerang - Mega Kartika Sari; Bhustomy Hakim; Evasaria Magdalena Sipayung; Marta Lenah Haryanti; Puguh Hiskiawan; Ozmar Azhari; Merryana Lestari; Gregorius Ivan Pamungkas Triwibowo (Bahasa Indonesia, 2026)
The rapid development of digital technology has not been fully accompanied by adequate information security literacy among students. This condition makes students more vulnerable to cyber threats such as phishing, fake applications, and the risks associated with using public Wi-Fi networks. This community service program aimed to provide information security education to students of SMA Negeri 8 Tangerang as an effort to support the strengthening of digital literacy and awareness of information security risks in daily activities. The program was conducted in four sessions using an educational and participatory approach, covering network and Wi-Fi security, fake apps, phishing, as well as password management and authentication. Post-activity evaluation was carried out through questionnaires, discussions, and participant feedback to examine participants’ responses regarding the relevance, clarity, usefulness, and level of engagement in the program. The evaluation results showed that 144 participants gave positive assessments of the program, with average scores above 3.60 on a scale of 1–4. These findings suggest that the participants perceived the materials as relevant, understandable, useful, and appropriate to their needs. Participant feedback also showed greater attention to digital security issues that are closely related to their daily lives. Overall, the program was well received and may support efforts to strengthen students’ digital literacy, particularly in recognizing information security risks in everyday digital activities.